2022
DOI: 10.1007/s11259-022-09979-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and epidemiology of severe fever with thrombocytopenia syndrome in dogs in the Republic of Korea: an observational study (2019–2020)

Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is a zoonotic disease with a high mortality rate for humans and cats. The clinical course and prognosis of SFTS in dogs remains unclear. In the present study, we investigated the clinical and epidemiological characteristics of SFTS virus (SFTSV) infection in dogs. All evaluated dogs exhibited an acute course and symptoms including fever (57.1%), anorexia (57.1%), depression (42.9%), and vomiting (35.7%). Thrombocytopenia was present in 45.5% of dogs, while jau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Moreover, another study demonstrated lower levels of white blood cell and platelet counts (below 100 counts/µL) in SFTSV-suspected cats from animal hospitals [45]. A reduction in platelet counts has also been documented as a clinical manifestation in SFTSV-affected dogs, with this phenomenon being noted in 45.5% (5 out of 11) of the observed cases [36]. This correlation with thrombocytopenia might be attributed, at least in part, to the sampling strategies in those studies.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Moreover, another study demonstrated lower levels of white blood cell and platelet counts (below 100 counts/µL) in SFTSV-suspected cats from animal hospitals [45]. A reduction in platelet counts has also been documented as a clinical manifestation in SFTSV-affected dogs, with this phenomenon being noted in 45.5% (5 out of 11) of the observed cases [36]. This correlation with thrombocytopenia might be attributed, at least in part, to the sampling strategies in those studies.…”
Section: Discussionmentioning
confidence: 90%
“…This correlation with thrombocytopenia might be attributed, at least in part, to the sampling strategies in those studies. In the Han et al's study [36], dogs that were exposed to ticks or displayed clinical symptoms resembling those of SFTS were included. However, in our current study, thrombocytopenia was the only selection criterion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, advancements in human research may lead to adapting these treatments for use in companion animals infected with SFTSV. Currently, companion animals are only given supportive care in veterinary hospitals, which includes antimicrobial and symptomatic treatments [ 186 , 187 ].…”
Section: Discussionmentioning
confidence: 99%
“…SFTSV was detected in 6.6% and 4% of the dogs in Laizhou Province and Penglai Province, respectively. Han et al reported 14 cases of dogs infected with SFTSV between April 2019 and December 2020 at animal hospitals in Korea [27]. These dogs showed some symptoms that were similar to those seen in cases of SFTS in humans and cats, but there were no deaths [28,29].…”
Section: Introductionmentioning
confidence: 85%